The Effect of Trade Liberalization on Firms' TFP (With an Emphasis on Tariff Rate) - Hosein Samsami; Ozra Daghmechi Firoz Jaei (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2012)
This paper investigates the trade liberalization (tariff rate decrease) effect on the total factor productivity (TFP) in Iranian industrial firms during 2000-2004. The TFP firms are determined by production function approach, and then the relationship between tariff rates and firm features (size, ownership type and the concentration degree of the industry relating to the firm) is analyzed. We showed that the impact of trade liberalization on the TFP has been positive, but the effects of firm features are different. Also, the impact of tariff rate on productivity in private firms is stronger than in the government owned firms. In addition, the impact of trade policies (tariff rates decreasing) on productivity in monopoly firms is stronger than competitive firms.